Kualitas Terjemahan Kohesi Leksikal Repetisi dalam Cerita Anak Jenjang Pembaca Dini - Putri, Devanni Kusuma; Sumarlam, Sumarlam (Universitas Sebelas Maret, 2024)
This study aims to find out the types of repetition and how they were translated in children-story books for emergent readers. The data were taken from five children story books, and they show the variety of repetitions. They are mesodiplosis, anaphora, epistrophe, sentence repetition, epizeuxis, dan syploce. Through four stages data analysis, this research found six translation techniques used in translating the repetitions: established equivalence, implicitation, explicitation, discursive creation, reduction, and paraphrase. Some of them contributed to change the types of repetition. The techniques are paraphrase, reduction, and discursive creation. The result shows that those three techniques decrease the accuracy for not accommodating the repetitions. However, there is only one technique that contributed to decrease the acceptability. It is discursive creation. Afterwards, the translation of the children story books for emergent readers gains 2.9 out of 3 in terms of accuracy and acceptability.